100 MeV O7+ ion irradiation induced electrochemical enhancement in NiBTC metal-organic framework based composite polymer electrolytes incorporated with ionic liquid. (8th May 2019) - Dutta, Rituraj; Kumar, Ashok
Abstract: Nickel 1, 3, 5-benzenetricarboxylate (NiBTC) metal-organic framework (MOF), has been synthesized by solvothermal method and dispersed in Poly (vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) polymer. The composite polymer electrolyte membranes were irradiated with 100 MeV O 7+ swift heavy ion (SHI) at different fluences and ionic liquid (IL) BMIMBF4 has been incorporated after irradiation. Increasing % uptake of IL has been observed upon IL incorporation as SHI irradiation can enlarge the micropore volumes of NiBTC-MOF by inducing missing linker defects. FTIR spectra depict shifting of carboxylate vibrational modes with increasing fluence suggesting elongation of metal-linker molecular bonds in NiBTC-MOF due to interaction of BF4 - anion of IL with unsaturated Ni metal nodes with increasing uptake of IL. Non-Debye relaxation ion dynamics has been revealed from dielectric modulus spectra and optimum ionic conductivity of 9.9 × 10 −3 Scm −1 is achieved for the nanocomposite membrane at the fluence of 3.3 × 10 12 ions cm −2 at 380 K. The frequency dependent AC conductivity increases with increasing fluence due to higher IL uptake as well as chain scission of the polymer segments. The electrochemical stability of the nanocomposite membrane increases with increasing fluence and attains a maximum value of 6.1 V at 3.3 × 10 12 ions cm −2 .